East Ural Radioactive Trace: cancer mortality over a 57-year period (1957-2014) - S. S. Silkin; L. Yu. Krestinina; A. V. Akleyev (Радиационная гигиена)
The objective of the current study was to assess the cancer mortality risk in the cohort of the exposed population on the territory of the East Urals Radioactive Trace over a 57-year follow-up period from 1957 to 2014 using individual doses. Materials and methods: At the end of September 1957 as a result of an accident in the cooling system of storage tanks with liquid radioactive waste, an explosion occurred on the territory of the Mayak PA which led to the formation of the East Urals Radioactive Trace. The population living in the contaminated settlements of the Chelyabinsk and Sverdlovsk regions has been affected by prolonged external and internal exposure. The cohort of individuals exposed in the territory of the East Urals Radioactive Trace numbers 21,384 people, of whom 2,055 persons had lived in Techa riverside settlements before the 1957 accident and received additional radiation exposure. The mean stomach dose for members of the East Urals Radioactive Trace cohort was 36 mGy, the maximum dose was 1130 mGy. The updated TRDS-2016 dosimetry system was used to assess individualized doses. Over the 57-year follow-up period of the cohort (1957-2014), 1294 deaths from cancer were registered in the catchment area. The number of person-years at risk was 511278. The analysis of the cancer mortality risk was carried out with the EPICURE statistical package using the Poisson regression method. Confidence intervals were calculated using the maximum likelihood method. Results: In the course of the cancer mortality analysis in the East Urals Radioactive Trace cohort over a 57-year period, a statistically significant excess relative risk of mortality per 100 mGy equal to 0.05 (95% CI: 0.002; 0.11, p = 0.04) was obtained in the entire East Urals Radioactive Trace cohort. If individuals who received additional exposure on the Techa River were excluded from the analysis, the value of the risk loses its statistical significance.